CHALLENGES OF ISLAMIC EDUCATION POLICY IN THE ARTIFICIAL INTELLIGENCE ERA: A LITERATURE REVIEW ON ETHICAL READINESS AND CURRICULUM - Diah Hestina Pratiwi; Subaidi Subaidi; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to critically examine the policy challenges facing Islamic education in the era of Artificial Intelligence (AI), with particular focus on ethical readiness and curriculum responses. Using a qualitative approach through systematic literature review, data were collected from reputable journal articles, academic books, proceedings, and policy documents published between 2022 and 2026, sourced from Google Scholar, Scopus, ERIC, and SINTA databases. Thematic content analysis was employed through open coding and thematic categorization to identify dominant patterns across the literature. The findings reveal that AI adoption in Islamic education in Indonesia is significantly hindered by weak regulatory frameworks, digital infrastructure disparities between urban and rural madrasahs, low digital competency among Islamic Religious Education (PAI) teachers, and insufficient ethical preparedness among educators. The Islamic ethical framework, particularly the maqāṣid al-sharī'ah approach, provides a robust foundation for governing AI use in Islamic educational contexts, while existing curriculum responses remain fragmented and unsystematic. This study concludes that the Ministry of Religious Affairs must urgently formulate AI governance regulations grounded in Islamic values, strengthen PAI teachers' digital literacy programs integrated with religious ethics, and promote integrative curriculum models that harmonize religious sciences with technological competencies, ensuring Islamic educational institutions produce morally grounded and technologically competent Muslim generations in the era of artificial intelligence.